2010
DOI: 10.5194/bg-7-2445-2010
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt sea surface pH change at the end of the Younger Dryas in the central sub-equatorial Pacific inferred from boron isotope abundance in corals (<i>Porites</i>)

Abstract: Abstract. The "δ 11 B-pH" technique was applied to modern and ancient corals Porites from the sub-equatorial Pacific areas (Tahiti and Marquesas) spanning a time interval from 0 to 20.720 calendar years to determine the amplitude of pH changes between the Last Glacial Period and the Holocene. Boron isotopes were measured by MultiCollector -Inductively Coupled Plasma Mass Spectrometry (MC-ICPMS) with an external reproducibility of 0.25‰, allowing a precision of about ±0.03 pH-units for pH values between 8 and 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 70 publications
9
66
1
Order By: Relevance
“…Such ratios, equivalent to ~30 ppm of boron for the most calcite-rich samples (~30%) are clearly lower than values observed for modern Porites (Douville et al, 2010;Gaillardet and Allegre, 1995;Hemming and Hanson, 1992) but are similar to concentrations measured in some calcite benthic foraminifera (Rae et al, 2011;Yu et al, 2007;Yu et al, 2010) and in inorganic calcite (Gabitov et al, 2014).…”
Section: Impact On δ 11 B B/ca and Reconstructed Phmentioning
confidence: 74%
See 3 more Smart Citations
“…Such ratios, equivalent to ~30 ppm of boron for the most calcite-rich samples (~30%) are clearly lower than values observed for modern Porites (Douville et al, 2010;Gaillardet and Allegre, 1995;Hemming and Hanson, 1992) but are similar to concentrations measured in some calcite benthic foraminifera (Rae et al, 2011;Yu et al, 2007;Yu et al, 2010) and in inorganic calcite (Gabitov et al, 2014).…”
Section: Impact On δ 11 B B/ca and Reconstructed Phmentioning
confidence: 74%
“…(Douville et al, 2010;Hemming et al, 1998;Krief et al, 2010;Pelejero et al, 2005;Shinjo et al, 2013b;Wei et al, 2009) (Lécuyer et al, 2002;Penman et al, 2013).Benthic foraminifera calcite presentlower δ 11 B (14-17‰), except for the high-magnesium calcite of large foraminifera (26‰),whilehigher values (21-25‰) were measured on planktonic species (Holcomb et al, 2015;Hönisch et al, 2008;Rae et al, 2011;Sanyal et al, 1996). For gorgonian calcite corals, recent studies of the genus Keratoisis (bamboo coral) revealed low values of δ 11 B, between 14 and 17‰ (Farmer et al, 2015).…”
Section: Impact On δ 11 B B/ca and Reconstructed Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Using these methods, long-term records of ocean pH variability have been established (15)(16)(17). However, these time series suffer from poor temporal resolution and do not resolve small-scale spatial heterogeneities of natural samples.…”
mentioning
confidence: 99%